Chlorella intake attenuates reduced salivary SIgA secretion in kendo training camp participants - Otsuki, Takeshi (BioMed Central, 2012)
BACKGROUND: The green alga Chlorella contains high levels of proteins, vitamins, and minerals. We previously reported that a chlorella-derived multicomponent supplement increased the secretion rate of salivary secretory immunoglobulin A (SIgA) in humans. Here, we investigated whether intake of this chlorella-derived supplement attenuated the reduced salivary SIgA secretion rate during a kendo training camp. METHODS: Ten female kendo athletes participated in inter-university 6-day spring and 4-day summer camps. They were randomized into two groups; one took placebo tablets during the spring camp and chlorella tablets during the summer camp, while the other took chlorella tablets during the spring camp and placebo tablets during the summer camp. Subjects took these tablets starting 4 weeks before the camp until post-camp saliva sampling. Salivary SIgA concentrations were measured by ELISA. RESULTS: All subjects participated in nearly all training programs, and body-mass changes and subjective physical well-being scores during the camps were comparable between the groups. However, salivary SIgA secretion rate changes were different between these groups. Salivary SIgA secretion rates decreased during the camp in the placebo group (before vs. second, middle, and final day of camp, and after the camp: 146 ± 89 vs. 87 ± 56, 70 ± 45, 94 ± 58, and 116 ± 71 μg/min), whereas no such decreases were observed in the chlorella group (121 ± 53 vs. 113 ± 68, 98 ± 69,115 ± 80, and 128 ± 59 μg/min). CONCLUSION: Our results suggest that a use of a chlorella-derived dietary supplement attenuates reduced salivary SIgA secretion during a training camp for a competitive sport.